Control Method for Lateral Vibration of High-Speed Trains under Crosswind - Zhao, Chuanhui; Kong, Xiangfeng (International Journal of Mechanical and Electrical Engineering, 2026)
This paper addresses the issue of lateral vibration of high - speed train car bodies caused by random track irregularity excitation and random wind excitation. It proposes an active control method based on the SABO - LQR algorithm and the secondary suspension system to enhance the running stability and safety of high - speed trains by suppressing the lateral vibration of the car body. First, a dynamic model of the cross - wind - vehicle - track system is established, taking into account both random track irregularity excitation and random wind excitation. Second, considering the difficulty in selecting the weight matrices Q and R during the design of the LQR controller, the SABO algorithm is used for iterative optimization to obtain the optimal weight matrices and the controller. Finally, the effectiveness of the proposed method is further verified through simulation. The results show that the proposed active control method based on the SABO - LQR algorithm and the secondary suspension system has the potential to effectively suppress the lateral vibration of the train car body. Compared with the passive suspension method and the LQR control method, this method can reduce the amplitude of the car body’s lateral vibration by 67.13% and 50.30% respectively, thus improving the riding comfort and the running stability of high - speed trains.